Connecting the Dots: What Drives the Linkages Between Green MSMEs and Large Industries in the Food-beverage Sector in East Java? - Dian Enggar Lintang Pertiwi; Pregita Alifia Putri; Fichrie Fachrowi Adli (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2026)
Despite national and regional efforts to advance the green economy agenda, linkages between micro and small enterprises (MSMEs) and large industries in Indonesia remain limited. East Java, a key contributor to the national economy with a substantial base of MSMEs, reports the lowest linkage rate in the food and beverage sector, falling below the national average. This gap reflects structural, institutional, and policy challenges that hinder partnerships between MSMEs and large industries. This study aims to identify key barriers, prioritize them based on urgency and impact, and formulate optimal policy strategies to strengthen linkages between green MSMEs and large industries in East Java’s food and beverage sector. A mixed-method approach was employed, combining practitioner and expert interviews with the Analytic Hierarchy Process (AHP) and Grey-TOPSIS to identify and prioritize 24 sub-barriers grouped into eight main categories. The analysis is grounded in primary data collected through focus group discussions and structured AHP questionnaires. Based on stakeholder evaluations, five policy alternatives were analyzed. Capital support and product upgrading were identified as the most effective measures to strengthen industrial linkages. The study recommends a direct approach, namely, local governments mapping green MSMEs with potential or existing ties to large industries, thereby enabling targeted interventions. For the indirect approach at the national level, fiscal and monetary instruments are proposed, including tax incentives for industries that support green MSMEs and preferential credit schemes offering low-interest financing. Additionally, collaboration through the hexahelix model, involving government, industry, academia, financial institutions, communities, and media, is essential to enhance industrial linkages and support green MSME development in East Java.